2015
DOI: 10.1002/er.3429
|View full text |Cite
|
Sign up to set email alerts
|

Pt/graphite catalyst for hydrogen generation by HI decomposition reaction in S-I thermochemical cycle

Abstract: SUMMARYHydrogen is an attractive energy carrier for future because of various reasons. Therefore its large scale production is the need of the hour. One of the ways to achieve this is sulfur iodine thermochemical cycle and HI decomposition reaction is one of the three reactions constituting the cycle. Pt/graphite catalysts with different loading of platinum were prepared by impregnating colloidal graphite with hexachloroplatinic acid solution followed by reduction under N 2 flow. The catalysts prepared have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…O'Keefe et al reported that Pt base catalyst showed the high activity to HI decomposition (about 20.2 and 22.5% HI conversion at 673 and 773 K, respectively). Similar results were reported on Pt base catalyst by several groups . Therefore, Pt is active to the HI decomposition reaction; however, HI decomposition activity is still low under a high space velocity (SV) and the stability is insufficient because of the deactivation by I 2 adsorption and reaction.…”
Section: Introductionsupporting
confidence: 82%
“…O'Keefe et al reported that Pt base catalyst showed the high activity to HI decomposition (about 20.2 and 22.5% HI conversion at 673 and 773 K, respectively). Similar results were reported on Pt base catalyst by several groups . Therefore, Pt is active to the HI decomposition reaction; however, HI decomposition activity is still low under a high space velocity (SV) and the stability is insufficient because of the deactivation by I 2 adsorption and reaction.…”
Section: Introductionsupporting
confidence: 82%
“…The influence of operating temperature on the electrolytic performance was analyzed in two opposite aspects. First, increase in temperature enhances the activity of species in the solution and increases the reaction kinetic rate because of the endothermic characteristic of HI decomposition . On contrary, the rising temperature reduces the local current density according to Equation .…”
Section: Resultsmentioning
confidence: 99%
“…Another study measured the boiling heat transfer coefficient of the sulfuric acid solution, which is required to design the sulfuric acid decomposer. Tyagi et al evaluated activity and stability of different catalysts for decomposition of hydriodic acid to choose suitable and stable catalyst for engineering application. Zhang et al proposed a detailed kinetic mechanism of homogeneous sulfuric acid solution decomposition and studied the effects of temperature, SO 3 /H 2 O ratio, residence time, and pressure on the decomposition rate of SO 3 to increase the SO 3 conversion.…”
Section: Introductionmentioning
confidence: 99%